Effect of prenatal exposure to kitchen fuel on birth weight - Yugantara Ramesh Kadam; Anugya Mimansa; Pragati Vishnu Chavan; Alka Dilip Gore (Wolters Kluwer Medknow Publications, 2013)
Background: Maternal exposure to kitchen fuel smoke may lead to impaired fetal growth. Objective: To study the effect of exposure to various kitchen fuels on birth weight. Methodology : Study type: Retrospective analytical. Study setting: Hospital based. Study Subjects: Mothers and their newborns. Inclusion Criteria: Mothers registered in first trimester with minimum 3 visits, non-anemic, full-term, and singleton delivery. Exclusion Criteria: History of Pregnancy Induced Hypertension (PIH), Diabetes Mellitus (DM), tobacco chewers or mishri users. Sample size: 328 mothers and their new-borne. Study period: Six months. Study tools: Chi-square, Z-test, ANOVA, and binary logistic regression. Results: Effect of confounders on birth weight was tested and found to be non-significant. Mean ± SD of birth weight was 2.669 ± 0.442 in Liquid Petroleium Gas (LPG) users (n = 178), 2.465 ± 0.465 in wood users (n = 94), 2.557 ± 0.603 in LPG + wood users (n = 27) and 2.617 ± 0.470 in kerosene users (n = 29). Infants born to wood users had lowest birth weight and averagely 204 g lighter than LPG users (F = 4.056, P < 0.01). Percentage of newborns with low birth weight (LBW) in wood users was 44.68% which was significantly higher than in LPG users (24.16%), LPG + wood users (40.74%) and in kerosene users (34.48%) (Chi-square = 12.926, P < 0.01). As duration of exposure to wood fuel increases there is significant decline in birth weight (F = 3.825, P < 0.05). By using logistic regression type of fuel is only best predictor. Conclusion: Cooking with wood fuel is a significant risk-factor for LBW, which is modifiable.